To promote experience sharing in urban transitions: An integrated framework of experience mining and triangulation - Guijun Li; Tanxiaosi Luo; Qian Liu; Yanqiu Song (Journal of Urban Management, 2022)
Many cities have put relentless efforts in promoting transformational changes to tackle urban challenges, accumulating considerable experiences and knowledge for other cities to learn. To reuse the successful experiences in an effective way, previous studies have developed experience mining systems, which adopt Case Base Reasoning as smart decision support systems to provide valuable references on how to manage and solve the current problems. However, the experience mining systems generally pay limited attention to the feasibility and applicability of transition experiences for the target city, making it challenging to validate results considering the complexity of urban transitions. To fill the gap, this paper proposes a methodological framework to evaluate matching degrees of past experiences by integrating experience mining with triangulation, aiming at selecting the most appropriate case for the target city from multiple perspectives. A case study of Beijing is further conducted, with different methodologies leading to distinguished results, which proves the necessity of employing various methods to enhance the validity of experience mining for urban transitions. It is envisaged that the integrated framework could help future practitioners and researchers to make better-informed choices with experience mining systems during experience learning or theory development in urban transitions.
Keywords: 710; Smart decision support system; Knowledge sharing; Experience transferability; Urban sustainability; Transition performance